Multicomponent Self‐Assembly with a Shape‐Persistent N‐Heterotriangulene Macrocycle on Au(111). Issue 4 (20th November 2014) - Cui, Kang; Schlütter, Florian; Ivasenko, Oleksandr; Kivala, Milan; Schwab, Matthias G.; Lee, Shern‐Long; Mertens, Stijn F. L.; Tahara, Kazukuni; Tobe, Yoshito; Müllen, Klaus; Mali, Kunal S.; De Feyter, Steven
Abstract Multicomponent network formation by using a shape‐persistent macrocycle (MC6) at the interface between an organic liquid and Au(111) surface is demonstrated. MC6 serves as a versatile building block that can be coadsorbed with a variety of organic molecules based on different types of noncovalent interactions at the liquid–solid interface. Scanning tunneling microscopy (STM) reveals the formation of crystalline bicomponent networks upon codeposition of MC6 with aromatic molecules, such as fullerene (C60) and coronene. Tetracyanoquinodimethane, on the other hand, was found to induce disorder into the MC6 networks by adsorbing on the rim of the macrocycle. Immobilization of MC6 itself was studied in two different noncovalently assembled host networks. MC6 assumed a rather passive role as a guest and simply occupied the host cavities in one network, whereas it induced a structural transition in the other. Finally, the central cavity of MC6 was used to capture C60 in a complex three‐component system. Precise immobilization of organic molecules at discrete locations within multicomponent networks, as demonstrated here, constitutes an important step towards bottom‐up fabrication of functional surface‐based nanostructures.